Edukasi Manfaat dan Diversifikasi Tanaman Obat dalam Menunjang Kesehatan dan Ekonomi Masyarakat Desa Mekarjaya Kecamatan Rumpin (Yayasan REDI Tiga Monas, 2023)
Mekarjaya Village is one of the villages in Bogor Regency, West Java Province, where the majority of the population earn a living as rice field and garden farmers. The types of plantations in Mekarjaya Village are dominated by rhizome/ medicinal plants such as ginger, turmeric, and others, which can be developed to become village characteristics as medicinal plant plantations. Problems related to the yield of rhizome plantations/ medicinal plants, namely (1) the benefits and potential of rhizome plants are not widely known by the public and (2) farmers have only planted a few types of rhizome, even though there are many other types of rhizome that have potential. This is what we are trying to overcome through educating the public, especially farmers, regarding the benefits and potential of the rhizome plant as a medicinal plant, followed by education regarding its diversification. Activities begin with scanning and mapping existing conditions and problems, reviewing previous programs to see alternative possible programs that can be run, social approaches to local government and the community to obtain common perceptions, coordination with stakeholders, the implementation of educational activities. The result of the activity is an increase in knowledge and understanding of the benefits and diversification of medicinal plants in the Mitra Tani Indah Farmer Group, Mekarjaya Village, Rumpin District.